Meningkatkan Hasil Belajar Pakbp Materi Aku Pribadi yang Unik dengan Model Problem Based Learning (PBL) untuk Kelas X Akuntansi SMK Negeri 1 Jorlang Hataran Tahun Pelajaran 2024/2025 - Afriani Samosir; Anselmus Yata Mones; Maria Margaretha Dwilinda (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This study aims to improve student learning outcomes in Catholic Religious Education and Character Education (PAKBP) in class X Accounting with the Problem-Based Learning model. The method used in this study is the classroom action research method. The tools used to collect data are observation and tests. The object of observation in this study is the students' character as depicted in the Pancasila student profile. Learning activities using the problem-based learning model are applied strictly based on the syntax or stages of the model. This study was conducted in two cycles, and each cycle consisted of planning, implementation, observation, and reflection activities. The results of the study indicate that student learning outcomes on the Unique Personal I material from cycle I were 72% to 89% in cycle II. The increase that occurred from cycle I to cycle II was 17%.